2020
DOI: 10.3389/fpsyg.2020.01037
|View full text |Cite
|
Sign up to set email alerts
|

Future Time Perspective and the Achievement of Optimal Best: Reflections, Conceptualizations, and Future Directions for Development

Abstract: Time is an interesting concept. For some cultural groups, time is an entity that exists only in the here and now, whereas for others it can be linear, emphasizing a person's past, present, and future. Many of us, while living in the "present moment," may also anticipate and project future goals, dreams, hopes, and ambitions. Indeed, from a positive point of view, future orientations are healthy and may direct one's focus, instill motivation and persistence, and mobilize the expenditure of effort. Existing rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 57 publications
(134 reference statements)
0
39
0
2
Order By: Relevance
“…Optimal functioning, or optimal best practice, is concerned with the maximization of a person's acquired knowledge, experience, and/or personal state of flourishing in a subject matter (e.g., feeling good about oneself) (Ngu et al, 2019). Over the past 5 years, we have made extensive theoretical, methodological, and empirical contributions to the study of optimal best practice, especially within the realm of academia (e.g., Ngu et al, 2019;Phan et al, 2019bPhan et al, , 2020b.…”
Section: The Importance Of Positive Psychology: a Brief Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimal functioning, or optimal best practice, is concerned with the maximization of a person's acquired knowledge, experience, and/or personal state of flourishing in a subject matter (e.g., feeling good about oneself) (Ngu et al, 2019). Over the past 5 years, we have made extensive theoretical, methodological, and empirical contributions to the study of optimal best practice, especially within the realm of academia (e.g., Ngu et al, 2019;Phan et al, 2019bPhan et al, , 2020b.…”
Section: The Importance Of Positive Psychology: a Brief Overviewmentioning
confidence: 99%
“…The relationship between L 1 and L 2, in its simplistic term, according to Phan et al's (2019b) recent study, is shown in (Phan et al, 2017(Phan et al, , 2019c, and a "state of flourishing" -in this case, defined as "a quantitative and qualitative difference between L 1 and L 2 [i.e., (L1−L2) ]." The theory of optimization (Phan et al, 2019c(Phan et al, , 2020b indicates that the achievement of L 2 from L 1 would require the activation and enactment of different types of educational (e.g., an appropriate instructional design: Ngu et al, 2018), psychological (e.g., belief of personal efficacy: Bandura, 1997), and psychosocial (e.g., the impact of the home environment: McCartney et al, 2007) agencies. Phan et al's (2019c) detailed proposition, interestingly, stipulated the positive effects of educational, psychological, and/or psychosocial agencies on the initiation of experience of "energy" (denoted as "E"), which would then activate the buoyancy of different psychological attributes (e.g., personal resolve).…”
Section: The Importance Of Optimal Best Practicementioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, of course, there are underlying operational mechanisms or principles (Tsai, 2008) that may contribute to assist and facilitate in the achievement of different life course trajectories. In the course of a person's life as a university student, say, he/she may rely on the process of optimization (Phan et al, 2017(Phan et al, , 2019a(Phan et al, , 2020b as an operational mechanism to assist with his/her schooling experiences. In a similar vein, another person's life trajectory as a senior citizen may consist of his/her social relatedness to others.…”
Section: What Is Life Education?mentioning
confidence: 99%